Accessory spleen hypertrophy mimicking colon cancer metastasis - Ates, I.; Yazici, O.; Yazilitas, D.; Ozdemir, N.; Zengin, N. (Experimental Oncology, 2016)
Accessory spleen is a congenital form of an ectopic splenic tissue. In this report, we present a case of a patient who was followed with the diagnosis of rectal and sigmoid colon cancer and an accessory spleen hypertrophy, which was thought to be colon cancer metastasis in the left hypochondriac region. After colectomy and splenectomy, accessory spleen that mimics cancer metastasis was diffrentially diagnosed using scintigraphy.